Edukasi Social Marketing Untuk Perubahan Prilaku Hidup Sehat Pada Masyarakat Desa (2024) - Rina Anggraini; Novica Jolyarni; Indri Putri Nikanti (Sevaka : Hasil Kegiatan Layanan Masyarakat, 2024)
Behavioral change toward a healthy lifestyle in rural communities remains a major challenge requiring strategic and sustainable approaches. Social marketing has proven to be an effective tool in promoting behavior change through communication, education, and empowerment. This study aims to examine the application of social marketing education to improve health awareness and behaviors among rural communities, focusing on hygiene, balanced nutrition, and prevention of infectious diseases. The research uses a qualitative descriptive approach involving observation, interviews, and secondary data analysis from governmental and non-profit health promotion programs. The findings indicate that community-based social marketing, supported by local leaders and media, successfully increased participation in health and nutrition activities by up to 68%. The study concludes that social marketing education can effectively promote healthy behavioral changes when integrated with local cultural values and active community engagement.